STUDI KELAYAKAN USAHA PEMBENIHAN IKAN KAKAP PUTIH DI BALAI PERIKANAN BUDIDAYA AIR PAYAU (BPBAP) SITUBONDO, JAWA TIMUR - Ima Kusumanti; Andri Iskandar; Syifa Sesaria; Ahmad Bohari Muslim (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
The production of white snapper, Lates calcarifer is mostly the result of high seas catching and still a little is obtained from aquaculture. The spawning technique at the Situbondo Brackish Water Cultivation Center is naturally by applying environmental manipulation with the spawning process occurring at night. The seed is sown in the morning or evening, with an acclimatization process for 5-10 minutes. The seeds that were stocked were 10 cm in size with an average weight of 100 g head-1, stocking density of 19 individuals m-3. The results showed that hatchery production was 531 360 fish per year consisting of 6 cycles with 450 000 stocking using 3 rearing tanks. The results of the study carried out showed that the analysis of the effort carried out at the BPBAP Situbondo for 3 months was an intensive activity seen from the production results which reached 472 320 3 cm 3 cm fry in 1 year, and the consumption size of white snapper. 500 g reaches 3 180 kg per year. The hatchery activities carried out at BPBAP Situbondo are feasible to be used as a business because the R/C Ratio obtained is about 2.3.